Application Of The Abacus Media To Improve Mathematics Learning Outcomes Of Class Ii Students Of SD Negeri 0703 Hutaraja Tinggi - Risya Yanti Hasibuan (Indonesian Journal of Basic Education, 2022)
The main question of this research is whether the learning media of the abacus can improve the mathematics learning achievement of the second grade students of SD Negeri 0703 Hutaraja Tinggi in the matter of counting. This study aims to improve the mathematics learning outcomes of grade 2 students of SD Negeri 0703 Hutaraja Tinggi in arithmetic operations. This type of research is Classroom Action Research, which consists of two cycles, which are carried out four times each. The research tools needed for this classroom action research are Learning Implementation Plans (RPP) and Assessment Forms. Data collection techniques used are tests and observations. This research includes quantitative and qualitative research. The research process includes planning, implementing actions, observing, and reflecting. The subjects of this study were the second grade students of SD Negeri 0703 Hutaraja Tinggi as many as 26 students. The results showed that in the first cycle, which was completed by 26 students, only 14 students or 54% met the Minimum Integrity Standards (KKM) or were in the very low category. And in cycle II, out of 26 students, 23 students or 88% completed the KKM. Based on the findings above, it can be concluded that the second grade students of SD Negeri 0703 Hutaraja Tinggi experienced an increase in their mathematics learning outcomes through the use of the abacus media